Executive Incentives, Corporate Governance and Tax Haven Utilisation: Evidence from Australian Financial Institutions. - Hill, Lesley Ellen (Curtin University, 2019)
This study extends prior research investigating the relation between firms’ use of tax haven jurisdictions and performance-based remuneration incentives of CEOs. Additionally, we assess the moderating role of corporate governance attributes on the relation between firms’ use of tax havens and the remuneration characteristics of CEOs in those firms. Based on a dataset of 1054 firm-year observations comprising publicly-listed Australian financial institutions over the 2008–2018 period, we find a positive and significant relation between firms’ use of tax havens and CEOs remuneration attributes. Governance attributes of CEOs pertaining to their tenure and level of gender diversity are significantly negatively related to tax haven utilization, and negatively moderate the relation between remuneration levels and tax haven use.